2022
DOI: 10.1089/mdr.2020.0432
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characteristics of Uropathogenic Escherichia coli Isolates from Kenya

Abstract: Introduction: Uropathogenic Escherichia coli (UPECs) are a significant cause of urinary tract infections (UTIs). In Kenya, UTIs are typically treated with b-lactam antibiotics without antibiotic susceptibility testing, which could accelerate antibiotic resistance among UPEC strains. Aim: This study determined the occurrence of UPEC producing extended-spectrum b-lactamases (ESBLs), the genes conferring resistance to b-lactams, and the phylogenetic groups associated with ESBLs in Kenyan UPECs. Methodology: Ninet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 28 publications
3
17
2
Order By: Relevance
“…Estimates of prevalence in these studies vary widely. One study of E. coli isolated from urine cultures of symptomatic patients identified ESBL-producers in 25% of the 94 samples tested 35 . Other studies have reported estimates ≥ 50% of Enterobacterales isolates classified as ESBL-producers among hospitalized patients, which mirror the high prevalence of colonized inpatients found in this study 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of prevalence in these studies vary widely. One study of E. coli isolated from urine cultures of symptomatic patients identified ESBL-producers in 25% of the 94 samples tested 35 . Other studies have reported estimates ≥ 50% of Enterobacterales isolates classified as ESBL-producers among hospitalized patients, which mirror the high prevalence of colonized inpatients found in this study 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, the resistance of Enterobacteriaceae to third-generation cephalosporins ranged from 6.2 to 30.8% among bacterial isolates in 2019 [ 52 ]. Muriuki et al [ 53 ] reports a similar finding for uropathogenic E. coli in Kenya between 2015 and 2018. The production of ESBL is probably due to the often-empirical prescriptions of ß-lactams, particularly in ambulatory medicine, while awaiting the results of ECBU.…”
Section: Discussionmentioning
confidence: 59%
“…Irrespective of the disease-presentation, the first key step in the pathogenesis of E. coli infections is the adherence to mucosal surfaces; subsequently, aggregation of bacteria inside the biofilm protects them from sheer forces and the onslaught of immune cells [52,69,70]. The relevant virulence-determinants of E. coli include adhesins (representative genes e.g., afa, CSH, fimH, fimP, pap, sfa, traT), toxins (cytotoxic necrotizing factor: Cnf1, haemolysin: hlyA, others: saT, vaT), suppressors of the immune system (shiA, sisA, sisB, sivH) and siderophores (aerobactin: aer, salmochelin: iro, enterobactin: ent, yersiniabactin: irp, others: iuD, iutA, yfcv), which all contribute to their survival and invasiveness in the infected host [71][72][73][74]. Surface factors, such as various adhesins have a pivotal role in mediating the adhesion of E. coli to biotic and abiotic surfaces, and the subsequent production of EPS.…”
Section: Discussion Review Of the Literaturementioning
confidence: 99%